Examining the effect of salbutamol use in ozone air pollution by people with exercise‐induced bronchoconstriction - Bennett T. Stothers; Andy Hung; Patric E. O. Gonçalves; Lulu X. Pei; Tessa van deKerkhof; Jem I. Arnold; Owen D. Harris; Nadine Borduas‐Dedekind; Andrew W. Sheel; Michael S. Koehle (Physiological Reports)
Abstract Previous studies based on animal models have raised concerns about salbutamol use in ozone air pollution with regard to ozone related lung injury. We conducted a double‐blind, randomized, placebo‐controlled crossover study including 18 subjects diagnosed with EIB by a eucapnic voluntary hyperpnea (EVH) test. Participants completed 30 min of standardized moderate to vigorous exercise in four conditions: ozone plus salbutamol; room air plus salbutamol; ozone plus placebo medication; and room air plus placebo medication. Spirometry, fraction of exhaled nitric oxide, and symptoms were measured before, immediately after, 30 min after and 1 h after exercise. Measurements between the four conditions were compared using percent change from pre to post exercise. There was a statistically significant difference between the salbutamol and placebo medication groups for spirometric variables including FEV1 (Estimate = 6.3, 95% CI: 4.23–8.37, p < 0.001). No differences were observed between ozone and room air exposures. There were no significant differences in FeNO response between experimental conditions. We found that salbutamol improved pulmonary function in individuals with EIB when exercising in ozone and did not increase eosinophilic airway inflammation as indicated by FeNO. This evidence suggests that it is safe for people with EIB to continue to use salbutamol as prescribed when ozone levels are elevated.